General organic chemistry: Problem solving approach - Jena, Satyaban; Rout, Laxmidhar (New Delhi: Indu Book Services, 2024)
Chapter 1 starts with aromaticity. Chapter 2 deals with acidity and basicity. Chapter 3 covers strain and NGP. Chapter 4 is Aliphatic Organic reactions. Chapter 5 is related to Aromatic organic reactions. Chapter 6 is related to Thermodynamic and kinetic control.
Includes Appendix
Keywords: Organic chemistry -- Aromaticity -- Strain and NGP -- Aliphatic organic reactions